Designing a cost accounting system at a winemaking company - Martins, I.; Major, M.; Fernandes, A. (International Journal of Entrepreneurship and Small Business, 2020)
This paper presents an experimental case study that follows an interventionist logic with the aim of designing a cost accounting system for a winemaking company. The system was designed with the main objective of determining the production costs of each variety of wine produced by the company, allowing the management to make more accurate and informed strategic decisions regarding price and cost control. Taking into consideration, the features of the company and its managerial information needs the chosen system to implement was the 'homogeneous cost pool method'. The study suggests that this method can be successfully implemented in the wine sector to inform decision-making processes and to enhance companies' financial performance.